STRATEGI EKONOMI POLITIK XIAOMI INC DALAM MEMASUKI PASAR SELULER (SMARTPHONE) DI INDIA TAHUN 2014-2017 - Sahara, Ricca Pala; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to explain the political economy strategy used by Xiaomi Inc in entering the mobile market (smartphone) in India. India as the world's second largest mobile market becomes a marketing target for Xiaomi. Xiaomi in an attempt to enter the smartphone market of India could defeat product of other smartphone vendors such as Samsung Group, Apple Inc, Lenovo Group and the other phone’s Companies. This research uses neo-liberalism perspective. It also uses Foreign Direct Investment theory by Stephen Hymer and level analysis is Groups. This research uses qualitative method and library research for references by collecting data from books, journals, articles, and news that come from various medias.In entering the Indian smartphone market, Xiaomi performs several political economy strategies that are implementing the government program of India “Make in India”, Implementing strategies developed by Xiaomi Triathlon, Strategy Sticky, Hunger Marketing and promoting competitive advantage so that Xiaomi products can enter the Indian smartphone market and become a favorite product of the users of smartphone India.Key words : Xiaomi smartphone, manufacture, strategy, make in india